Legal Protection for Victims of Criminal Acts of Theft with Aggravation Based on Pancasila Justice (Case Study of Decision Number 160/Pid.B/2024/PN Sda) - Videawati, Videawati; Gunarto, Gunarto (Jurnal Hukum Khaira Ummah, 2025)
Abstract. This study aims to analyze the legal protection afforded to victims of the criminal act of aggravated theft from the perspective of Pancasila justice, using Case Decision Number 160/Pid.B/2024/PN Sda as the focal point. The research addresses two main questions, how is legal protection for victims of aggravated theft conceptualized within the framework of Pancasila justice? and what are the obstacles and potential solutions in implementing such protection. The research adopts a normative juridical approach by examining statutory regulations, legal doctrines, and relevant court decisions as primary and secondary legal sources. The values of Pancasila particularly the second and fifth principles serve as the philosophical foundation to assess the extent to which the current criminal justice system reflects substantive justice for victims. The findings indicate that the legal protection provided to victims of aggravated theft remains largely formalistic and does not fully embody the substantive justice envisioned by Pancasila. Victims are often treated merely as complainants or witnesses, rather than as parties entitled to the restoration of their rights. Challenges identified include limited regulatory frameworks addressing victims' rights comprehensively, the lack of justice-oriented perspectives in judicial processes, and minimal implementation of restorative justice measures.